A vegetable oil and/or fats. - Azlan, Azrina; Ismail, Amin (2008)

(untitled)
The present invention relates to edible oil having high polyphenolic content compared to virgin olive oil and palm oil. Disclosed and claimed related to the present invention are liquid oil and/ semi-solid extract of pulp and skin mixture form Canarium odontophyllum, and potential uses in various food preparations and applications. Additionally, the disclosed and claimed related to the present invention can be used in various food applications as sources of fat in the form of liquid or semi-solid. The present invention further relates to antioxidant activity and capacity of both pulp and flesh of Canarium odontophyllum that is highly correlated to the polyphenolic content of the oil extract. Further, the disclosed and claimed of the present invention can be used as natural source for antioxidant, as food preservative and additives as well as part of food ingredient in normal food preparation and preparation of various commercial products and used as base in pharmaceutical and cosmetic formulations.